Evaluasi Pembelajaran Matematika Pada Boarding School Berdasarkan Model Cipp - Santika Lya Diah Pramesti (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2020)
Learning mathematics can be monitored to what extent its development by conducting an evaluation process. One of the evaluation models of mathematics learning uses the CIPP evaluation model. This research is to find out the syntax of CIPP model mathematics learning evaluation and the results of the CIPP model mathematics learning evaluation in MAN IC in Pekalongan City. Data analysis techniques used qualitative research case study analysis that was evaluative. CIPP evaluation model is an evaluation model consisting of context, input, process, and product. In context evaluation, mathematics learning has covered most of the quality and appropriateness of mathematics learning goals according to the madrasa vision and mission. In context, the analysis results obtained by the percentage classified in the category of very good. Judging from the input that includes students, curriculum, teaching materials, teachers, and infrastructure to achieve the objectives of the mathematics learning program are in the very good category. Evaluation of the process of learning mathematics includes evaluating the requirements for implementing learning and implementing learning. In the process, the percentage is categorized as good. Judging from the product evaluation regarding teacher learning tools and learning achievement included in the very good category. Keywords: CIPP, Evaluation, Mathematics Learning Abstrak Pembelajaran matematika dapat dipantau sejauhmana perkembangannya dengan melakukan proses evaluasi. Model evaluasi pembelajaran matematika salah satunya menggunakan model evaluasi CIPP. Penelitian ini untuk mengetahui sintaks evaluasi pembelajaran matematika model CIPP dan hasil evaluasi pembelajaran matematika model CIPP di MAN IC Kota Pekalongan. Teknik analisis data menggunakan analisis penelitian kualitatif studi kasus yang bersifat evaluatif. Model evaluasi CIPP merupakan model evaluasi yang terdiri dari context (konteks), input (masukan), process (proses), dan product (produk). Evaluasi context, pembelajaran matematika telah mencakup sebagian besar kualitas dan kesesuaian tujuan pembelajaran matematika sesuai visi dan misi madrasah. Secara context, hasil analisis diperoleh persentase tergolong dalam kategori sangat baik. Dilihat dari input yang mencakup siswa, kurikulum, bahan ajar, guru, dan sarana prasarana untuk mencapai tujuan program pembelajaran matematika berada pada kategori sangat baik. Evaluasi process pembelajaran matematika meliputi evaluasi persyaratan pelaksanaan pembelajaran dan pelaksanaan pembelajaran. Secara process diperoleh persentase tergolong dalam kategori baik. Dilihat dari evaluasi product mengenai perangkat pembelajaran guru serta prestasi belajar termasuk pada kategori sangat baik. Kata kunci: CIPP, Evaluasi, Pembelajaran Matematika